Challenges of intellectual property in the information society - Huarag Guerrero, Enrico Marcel (2018)
The progressive but unstoppable implementation of the Information Society has led to a number of changes in the way individuals understand creative activity and the value of intellectual property.However, the intellectual property system, especially in the case of copyright, has not been able to adapt to these new changes, seeking to tighten the rules of sanction. The enforcement does not seem to work, because the consequences of the digitization, the lack of support and the dematerialization of protected contents have not been understood.Although in the field of patents there is a progressive movement to the flexibilization of the system, the same has not happened in copyright, thus hindering the development of new business models.